(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Installation of Wave Energy Converters is typically not considered at locations with low wave energy density. This condition is quite common in many sites worldwide, at least during part of the year, and include bays, sheltered areas, lakes, and the vast majority of locations within the tropics. In this context, a Wave Amplifier (WA) would be a device or structure aimed to increase locally the wave energy density and enhance the WEC’s performance and power output. Due to its seasonal role, the WA would require to be a rapidly deployable device embracing one or several WECs. The proposed WA consists of a pair of (sea)water filled watertight bladder tubes pressurized to a desired level of bending stiffness. Typically, the two bladder units are arranged in a ’V’ formation. The open ‘V’ of the bladder system faces the direction of the incoming waves. As a standard floating breakwater, the structure would reflect and transmit some of the wave energy. The configuration of the tubes create a (constructive) interference area bounded by the ‘V’ with incident and re-reflected waves, thereby enhancing their amplitude. Each bladder tube have been designed and fabricated up to a diameter of 9 m (30-ft) and more than hundred meters long. The choice of full-scale tube diameter and length is based upon both the water depth in the intended area of operation and the site wave conditions. The bladder comprises a sealed membrane tube containing pressurized water encased within an exoskeleton structural matrix of webbing that resists the primary tensile loads. The pressurized floating bladders resists the wave forces by stiffening the exoskeleton support structure. The WA requires to be attached to a mooring system at either ends to keep it in place. Each bladder considers built-in buoyancy which floats it at the nominal water surface. Buoyancy tubes are connected to the top of the bladder to minimize wave overtopping and to stabilize roll. A physical model study of a Wave Amplifier (WA) as described above, was conducted at the O.H. Hinsdale Wave Research Laboratory, Oregon State University, to evaluate the wave amplification characteristics and its dependency on the incident wave conditions (i.e. wave height, period and direction), water depth (e.g. under-keel clearance), bladder properties (internal pressure and diameter) and bladder layout. The physical model tests were carried out in the Directional Wave Basin and were supported by the DOE-funded TEAMER Program. A 1:24 scale model of a pair of 107 m (350-ft) long by 6.1m (20-ft) diameter water filled and pressurized bladders was tested over a range of regular and random sea-state conditions. The basin was fitted with 16 wave gauges and Qualisys Motion Tracking System was used to measure the free surface within the ‘V’ of the WA using floating reflective markers, while additional markers were attached to the bladder to measure its three-dimensional deformation under waves. The results indicate that the WA can increase the wave energy density in the bounded area by up to 90% and 80% for regular and random waves, respectively.